2022
DOI: 10.3390/plants11131627
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Diversity and Anti-Insect Activity Evaluation of Essential Oils Extracted from Five Artemisia Species

Abstract: As a source of aromatic plants, the genus Artemisia has long been considered to have the potential to develop plant pesticides. In this study, components of essential oils from A. dalai-lamae, A. tangutica, A. sieversiana, A. tanacetifolia and A. ordosica were identified by GC-MS. A total of 56 constituents were analysed, and each species consisted of 9 to 24 constituents. Principle component analysis (PCA) revealed that A. dalai-lamae, A. tangutica and A. tanacetifolia are characterised by monoterpene hydroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…The oils overall showed a weak pharmacological effect (anti-inflammatory) in activating the human neutrophils; however, the relatively higher effect was showed by A. tridentata due to the presence of farnesene (smaller amounts) [ 43 ]. A recent study of various Artemisia species suggested the presence of sufficient amounts of oxygenated monoterpenoids that imparted potential insecticidal activities (LD 50 = 17–52 μg/mL), a possible therapeutic application for environmentally friendly pesticides [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The oils overall showed a weak pharmacological effect (anti-inflammatory) in activating the human neutrophils; however, the relatively higher effect was showed by A. tridentata due to the presence of farnesene (smaller amounts) [ 43 ]. A recent study of various Artemisia species suggested the presence of sufficient amounts of oxygenated monoterpenoids that imparted potential insecticidal activities (LD 50 = 17–52 μg/mL), a possible therapeutic application for environmentally friendly pesticides [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The essential oils of Artemisia absinthium L. and Artemisia dracunculus L. displayed noticeably fumigant toxicity, with LC 50 values of 2.60 and 1.08 µL/L, respectively, against eggs of the potato tuber moth Phthorimaea operculella (Zeller) [32]. Toxicity of essential oils isolated from four Artemisia species, including A. dalai-lamae Krasch., A. tangutica Pampanini, A. tanacetifolia L., and A. ordosica Krasch., where 24 LC 50 values of 25.7, 17.4, 41.9, and 21.7 µg/insect, respectively, against the red flour beetle Tribolium castaneum Herbst were documented [33]. However, in the present study, the insecticidal effects of A. fragrans essential oil was evidenced for the first time, in which the essential oil with a 24 h LC 50 of 22.13 µL/L had noteworthy fumigant toxicity against the adults of T. confusum.…”
Section: Discussionmentioning
confidence: 97%
“…Based on the comparison of the spectra from the library of the National Institute of Standards and Technology (NIST), combined with analysis of plant VOCs in published literature, volatile compounds of samples were identified. In a previous study, monoterpenes were identified in PVOCs of Artemisia species. These components identified belong to different monoterpenoids structures: α- pinene, β- pinene, sabinene limonene, 4-terpineol, etc.…”
Section: Methodsmentioning
confidence: 99%